(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The peristaltic transport of a Casson fluid in a vertical permeable channel with suction and injection by Galerkin method is studied.. The mathematical modeling is realized with an approximation of the extended wave length and a low Reynolds number. The mathematical solution is obtained for the velocity field, pressure gradient, frictional force within the reference wave system over one wavelength. The results of various parameters on pressure rise characteristics and frictional forces are discussed graphically. It is observed that the pressure rise decreases because the slip parameters and suction/injection parameter increases and increases because the amplitude increases.